First description of the male of Glyphiulus formosus (Pocock, 1895) (Diplopoda: Spirostreptida: Cambalopsidae) from China - Jiang, Xuan-Kong; Hennen, Derek A.; Chen, Hui-Ming; Xie, Zhi-Cai (Zootaxa, 2020)
The male of Glyphiulus formosus (Pocock, 1895) is described for the first time based on specimens collected from Shenzhen, Guangdong, China. According to the male sexual characters, this species is verified to be a member of the G. javanicus group. In addition, a DNA barcode of the partial COI gene of G. formosus is provided.